FORMULASI DAN ANALISIS YOGHURT TEMPE SEBAGAI ALTERNATIF MINUMAN UNTUK PASIEN DIABETES MELLITUS - Yohannes Willihelm Saleky; Agus Sulaeman (Jurnal Gizi dan Dietetik, 2026)
One of the most important aspects of managing diabetes mellitus is diet. Yogurt's high nutritional content (probiotics, calcium, and protein), has made it a vital part of diets for those with diabetes mellitus. Tempeh has lots of potential as a substitute ingredient for yogurt, especially for people with diabetes. The purpose of this study was to evaluate the organoleptic characteristics and nutritional value of tempeh-based yogurt. Research design used was experimental. The independent variable was the concentration of tempeh in three levels, which influenced the organoleptic qualities and macronutrient content. The product development and organoleptic test from semi-trained panelists were done at Poltekkes Bandung, while nutrient analysis was done at The Sibaweh Laboratory, Bandung. The significancy of 0.05 was used to decide the statistical tests. The results of the hedonic test showed that formulation F2 had the highest ratings for viscosity and aroma, while formulation F3 received the top preference scores for color, taste, and overall acceptability. Nutritional analysis showed that F2 was the best, with the maximum energy (79 kcal) and protein content (15 g). The F2 is suggested for additional research and development, including sophisticated laboratory testing and possible use as an enteral nutrition product for diabetic patients.